The Dialectics of Subservience and Empowerment: Feminine Epistemologies in Amish Tripathi’s Sita: Warrior of Mithila - Vijay Karthic R (ILN Journal: Indian Literary Narratives, 2025)
This research article investigates the dialectics of subservience and empowerment as embodied by the female figures in Amish Tripathi’s Sita: Warrior of Mithila, with particular attention to Sita, Kaikeyi, and Manthara. It argues that Tripathi’s mythological retelling reconfigures the traditional Ramayana archetypes of passive devotion, villainous ambition, and manipulative marginality into nuanced subjectivities that foreground feminine epistemologies of power, resistance, and moral reasoning. By granting narrative authority and psychological depth to these women, Tripathi destabilizes the patriarchal binaries of the epic tradition and reimagines the feminine as central to the articulation of dharma. The article situates this transformation within the larger cultural and philosophical discourses of gender in Indian mythology, demonstrating how the series engages with questions of justice, agency, and ethical responsibility. Furthermore, it explores how the multi-linear narrative structure, political recontextualization, and dialogic engagement with classical traditions generate a feminist mythography that resonates with contemporary debates on gender equality. In analyzing the coexistence of constraint and agency within the experiences of Tripathi’s women, the article contends that empowerment in mythology is always negotiated, never absolute. Ultimately, it argues that the Sita: Warrior of Mithila exemplifies how myth, when reimagined through feminist lenses, functions not only as cultural memory but also as a dynamic space for the rearticulation of social ethics in the modern age.